Report of the Working Group on Mid-Term Appraisal of Financial Resources for the Eighth Five Year Plan - Planning Commission (Planning Commission, 1995)
The Working Group Report on the Mid-Term Appraisal of Financial Resources for the Eighth Five Year Plan evaluates the adequacy and performance of resource mobilisation in India during 1992–1997, with particular emphasis on the state sector. The study reveals substantial shortfalls in planned public sector outlays due to weak revenue generation, declining surpluses from state public enterprises, and increased dependence on borrowings. Rising debt servicing obligations significantly constrained fiscal space, limiting expenditure on social and infrastructure sectors. The report highlights wide inter-state disparities in financial performance and underscores the growing reliance on central assistance. It recommends strengthening additional resource mobilisation strategies, improving efficiency of state-level public enterprises, diversifying funding sources, and reorienting expenditure priorities to ensure fiscal sustainability and effective implementation of development objectives.
Planning Commission New Delhi June, 1995
Planning Commission New Delhi June, 1995
Keywords: Eighth Five Year Plan; Financial Resources Appraisal; Planning Commission of India; Resource Mobilisation; State Finances; Public Sector Outlay; Balance from Current Revenues; Additional Resource Mobilisation; State Public Sector Enterprises; Deficit Financing; Central Assistance; Fiscal Sustainability